Complexity of persistent type II endoleak associated with sac expansion after endovascular abdominal aortic aneurysm repair. (December 2015) - Spanos, Konstantinos; Rountas, Christos; Giannoukas, Athanasios D
Type II endoleak after endovascular aortic aneurysm repair still remains the Achilles' heel of the treatment, the source of which regularly is difficult to identify and treat. We present a patient with a persistent type II endoleak associated with a continuous aneurysm sac expansion after endovascular aortic aneurysm repair for which many diagnostic modalities were used during his follow-up such as duplex scan, computed tomography angiography and magnetic resonance angiography. Attempts were undertaken to treat the source of endoleak including coil micro-embolisation of lumbar arteries and subsequent open ligation of the inferior mesenteric artery, but they failed to eliminate the endoleak. Finally, a middle sacral artery was identified as the source of the endoleak. At that time, the patient was subjected to surgery for sigmoid carcinoma, and simultaneously, a ligation of the sacral artery was undertaken which eventually eliminated the endoleak completely. This case highlights that type II endoleak may be evoked by various sources and there can be a great difficulty to identify these feeding vessels; thus, careful planning for its management is mandatory.